Comparison of Parallel Dowel-Bearing Strength of Mengkulang, Kempas and Pine Glulam between ASTM D 5764-97a and BS EN 383: 2007 - Jihan A. Malek, Nor; Hassan, Rohana; Ibrahim, Azmi; M. H. Almanea, Hussein; H. Hean, Tee (International Journal of Engineering and Technology, 2018)
Dowel-bearing strength is a significant parameter for designing wood connection. The strength of timber connection can be influenced by the bolt diameter, wood grain direction either parallel or perpendicular, thickness of wood, moisture content and other parameters. The dowel-bearing strength test was conducted with a 12 mm bolt diameter dowel, for three different types of timber species, which were mengkulang (Heritiera sp.), kempas (Koompassia malaccensis) and pine (Pinus sp.) glulam. The dowel was placed parallel to the timber grain direction with a glue line at the center of the half-hole test. The 5% diameter offset load (F5%) for dowel-bearing strength (Fy) was determined by using the ASTM D 5764-97a whereas the dowel-bearing strength (Fh) was determined based on BS EN 383: 2007. The results of the three different types of wood showed that the Malaysian timber kempas and mengkulang were 51.740% and 32.966%, respectively, which were higher than the European timber pine. The results of the dowel-bearing strengths (Fh), which were based on the BS EN 383: 2007 gave higher values compared to ASTM D 5764-97a.Â Â